Pengaruh Current Ratio, Asset Size, dan Earnings Variability terhadap Beta Pasar - Ahim Abdurahim (Journal of Accounting and Investment, 2003)
The research objective was to determine the effect of variable accounting ie :, current ratio, asset size and earnings variability of the market beta. This study used 72 samples. Analyzer used to test the hypothesis that regression. Previous methods of Fowler and Rorke (1983) to adjust the market beta, and BLUE test is used to test classic assumptions of the independent variables are multikolinearitas, heteroskedasitas with Breushch-Pagan-Godfrey test, and autocorrelation with BG (The Breussh-Godfrey). The results found that the hypothesis H1a, H1b, H1c, and H2a powered means no influence current ratio, asset size and earnings variability of the market beta, both individually and simultaneously.